The Contoured Anterior Spinal Plate A Nursing Perspective - Atwell, Ellen (Operating Room Nurses Association of Canada Journal, 1993)
The Contoured Anterior Spinal Plate (CASP) system was developed by Dr. G. Armstrong (Chief of Orthopaedic Surgery, Ottawa Civic Hospital) with the help of the National Research Council of Canada for anterior stabilization of the thoracolumbar spine. The plates are designed with a contoured fit to accommo- date the curvature of the vertebral bodies. Multiple screw holes allow at least three screws per vertebra.